Hermeneutika Teks Abdul Karim Soroush: Solusi Epistemologis Atas Kontestasi Klaim Muradullah - Zaeni, Ahmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research aims to reveal Abdul Karim Soroush's Text Hermeneutics as an epistemological solution to the reliability of classical Ulumul Qur'an which gave birth to the contestation of mura>dullah's claim in interpretation when faced with contemporary reality. The type of this research is a literature study, because it relies on non-numerical data. While the data analysis technique used is the Miles and Huberman model. While the data analysis method used is content analysis and linguistic analysis. This research produces three important points. First, by using the hermeneutic theory of al-Qabd wa al-Bast (theory of shrinkage and expansion), Soroush shows that the reliability of classical Ulumul Qur'an is not for all times, but it is shrinking and expanding. Interpretation will never be final and demands a fresher dynamism of Ulumul Qur'an according to the demands of the times. Second, mura>dullah's claim on an interpretation under the pretext of the objectivity of interpretation is impossible, because the text has multiple meanings and that is the true will of Allah. Third, the interpretation that is in accordance with muradullah is an interpretation that is methodological (based on theory) even though it produces different meanings and interpretations (interpretive pluralism).